Optimalisasi Peran Guru Kimia dalam Penerapan Kelas Inklusi (Sekolah Menengah Atas) - Fauzan Abrori (CV. Multi Kreasi Media, 2023)
The purpose of this study was to explore and optimize the role of chemistry teachers in implementing inclusive classes in high schools, taking into account the problems that chemistry teachers might face in the learning process. This research method uses a qualitative approach. The results of this study indicate that optimizing the role of chemistry teachers in implementing inclusive classes in high schools is a process that requires proper planning and adjustments to ensure that students with special needs receive inclusive and effective learning. Chemistry teachers can maximize their role in implementing inclusive classes by collaborating with other staff at school, using a more structured learning approach or learning techniques that are more varied, and providing additional assistance to students in need. In addition, teachers must also continue to learn and develop their own knowledge and skills to be able to provide the best learning environment for all students, including those with special needs.